Enhancement of local electric field in core-shell orientation of ellipsoidal metal/dielectric nanoparticles - Ismail, A.A.; Gholap, A.V.; Abbo, Y.A. (Condensed Matter Physics, 2017)
In this paper it is shown that the enhancement factor of the local electric field in metal covered ellipsoidal nanoparticles embedded in a dielectric host matrix has two maxima at two different frequencies. The second maximum for the metal covered inclusions with large dielectric core (small metal fraction p) is comparatively large. This maximum strongly depends on the depolarization factor of the core L⁽¹⁾z , keeping that of the shell L⁽²⁾z constant and is less than L⁽¹⁾z . If the frequency of the external radiation approaches the frequency of surface plasmons of a metal, the local field in the particle considerably increases. The importance of maximum value of enhancement factor |A|² of the ellipsoidal inclusion is emphasized in the case where the dielectric core exceeds metal fraction of the inclusion. The results of numerical computations for typical small silver particles are presented graphically.